Reality Group Counseling to Improve Adolescent Self-Concept from Broken Home Family - desy humaira (Analitika, 2017)
Adolescents from broken home family often have psychological problems that are internal which will affect their behavior in the environment. This condition is experienced by six teenagers (3 males and 3 females) with broken home family background which complained by teachers that they often break the rules at school. Based on the assessment results, all six teenagers are experiencing the same problems that is negative view of themselves due to the lack of need for affection and acceptance from families who no longer intact. This negative self concept causes them to behave in a less responsible. Interventions conducted in groups which is reality group counseling through seven sessions. As the result, all six clients experienced enhancement of self-concept that encourages them to do more positive behavioral changes.